2021
DOI: 10.1039/d1tc00414j
|View full text |Cite
|
Sign up to set email alerts
|

Coexistence of intrinsic piezoelectricity and nontrivial band topology in monolayer InXO (X = Se and Te)

Abstract: The combination of piezoelectricity with other unique properties (like topological insulating phase and intrinsic ferromagnetism) in two-dimensional (2D) materials is much worthy of intensive study. In this work, the piezoelectric...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 77 publications
0
20
0
Order By: Relevance
“…20 Whereas, few studies about the combination of 2D TIs and piezoelectricity have been reported to my knowledge. Although SrAlGaSe 4 is proposed to be a piezoelectric QSH insulator (PQSHI) at 1.01 biaxial strain, 21 and the InXO (X = Se and Te) also exhibits piezoelectricity and band topology simultaneously, 22 their band gaps, as always, are so small that thermal excitation will easily destroy the nontrivial phases. Therefore, we aim to design PQSHIs with sizable band gaps to broaden the practical applications and further promote the development of multifunctional 2D materials.…”
Section: Introductionmentioning
confidence: 99%
“…20 Whereas, few studies about the combination of 2D TIs and piezoelectricity have been reported to my knowledge. Although SrAlGaSe 4 is proposed to be a piezoelectric QSH insulator (PQSHI) at 1.01 biaxial strain, 21 and the InXO (X = Se and Te) also exhibits piezoelectricity and band topology simultaneously, 22 their band gaps, as always, are so small that thermal excitation will easily destroy the nontrivial phases. Therefore, we aim to design PQSHIs with sizable band gaps to broaden the practical applications and further promote the development of multifunctional 2D materials.…”
Section: Introductionmentioning
confidence: 99%
“…The coexistence of intrinsic piezoelectricity and ferromagnetism, namely piezoelectric ferromagnetism (PFM), has been predicted in 2D vanadium dichalcogenides, VSi 2 P 4 , CrBr 1.5 I 1.5 and InCrTe 3 [16][17][18][19] . The combination of piezoelectricity with topological insulating phase has also been achieved in monolayer InXO (X=Se and Te) 20 and Janus monolayer SrAlGaSe 4 21 . A natural idea is to search for PQAHI with piezoelectricity, topological and FM orders.…”
Section: Introductionmentioning
confidence: 92%
“…On the other hand, considering that a single physical property is sometimes difficult to meet the needs of practical appli-cations, 2D multifunctional materials that combine QSH states and other physical properties, such as piezoelectricity, 18,19 ferroelectricity 20 and ferroelasticity, 21 are becoming a research hotspot in 2D topological materials. The coexistence of piezoelectricity and QSH states can bring a great breakthrough in the field of low-power piezoelectric devices.…”
Section: Introductionmentioning
confidence: 99%